Why we scratch: Function and dysfunction. Issue 12 (26th June 2019) - Sanders, Kristen M.; Fast, Katharine; Yosipovitch, Gil
Abstract: Itch is a common sensation that drives an intense urge to scratch. Itch and scratching have persisted in humans and many other species, suggesting that they play an important role in survival. This commentary discusses the function of itch as a danger signal, why itch feels unpleasant and why we feel relief and pleasure when we scratch an itch. In addition, we explore the ways that this system becomes dysfunctional in conditions of chronic itch and important implications for treatment.